The use of medicinal plants and herbal medicines for patients in chemotherapy in an oncology center of Ijuí/RS - Gislaine Tisott Dal Molin; Aline Williens Cavinatto; Christiane de Fátima Colet (O Mundo da Saúde)
Cancer patients seek to alternative and complementary treatments searching for rapid improvement, especially medicinal and herbal plant. This work objective is to evaluate the use of medicinal plants and herbal medicines in patients with cancer who are treated at the High Complexity in Oncology Center (CACON) in the city of Ijuí/RS. Data were collected from June to December 2013. Being included all users who performed intravenous chemotherapy. It was interviewed 130 patients, 62% female, with a mean age of 56 years. The medicinal plants most frequent were Annona muricata (26%), Aloe vera (23%) Euphorbia tirucalli (8.8%). For plants used in this study, there were no references to present scientific evidence of its pharmacological action for cancer treatment, proving the lack of education of the patients on medicinal plants. It was found that the indication of use of medicinal plants were mostly by family (68.5%) and friends (13.8%), without monitoring, guidance and medical knowledge. The lack of information and monitoring of users can be a warning to health authorities, to improve the oversight and promote the development of studies focusing on ways of its use and the risks of medicinal plants.